Ultrasound assessment of peripheral nerve pathology in neurofibromatosis type 1 and 2. Issue 5 (May 2017) - Winter, Natalie; Rattay, Tim W.; Axer, Hubertus; Schäffer, Eva; Décard, Bernhard F.; Gugel, Isabel; Schuhmann, Martin; Grimm, Alexander
Highlights: Ultrasound is an easy-to-apply tool for visualization of neurofibromas and schwannomas in NF1 and NF2. NF1 shows generalized nerve enlargement with diffuse plexiform neurofibroma, while NF2 shows focal schwannomas of single fascicles in most patients. Ultrasound can facilitate further analysis of peripheral nerve tumors in NF1 and NF2 by targeted MRI. Abstract: Objective: The neurofibromatoses (NF) type 1 and 2 are hereditary tumor predisposition syndromes caused by germline mutations in the NF1 and NF2 tumor suppressor genes. In NF1 and 2, peripheral nerve tumors occur regularly. For further characterizing nerve ultrasound was performed in patients with NF1 and 2. Methods: Patients with established diagnosis of NF1 ( n = 27) and NF2 ( n = 10) were included. Ultrasound of peripheral nerves and cervical roots was performed during routine follow-up visits. Healthy volunteers were studied for comparison. Results: In patients with NF1, median cross-sectional area (CSA) of most nerves was significantly increased compared to controls and to NF2 due to generalized plexiform tumors, which arose out of multiple fascicles in 23 of 27 patients (85%). These were often accompanied by cutaneous or subcutaneous neurofibromas. In NF2, the overall aspect of peripheral nerves consisted of localized schwannomas (80%) and, apart from that, normal nerve segments. Conclusion: Nerve ultrasound is able to visualize different nerve pathologies in NF1 and NF2. It is a precise and inexpensive screening method for peripheral nerve manifestation in neurofibromatosis and should be considered as the first choice screening imaging modality for all peripheral nerves within reach of non-invasive ultrasound techniques. Significance: Ultrasound patterns of peripheral nerve pathologies are described for the first time in a large cohort of patients with NF1 and NF2. It is a suitable screening tool and enables targeted MRI analysis.